Quando me vi negra: a formação da identidade da mulher negra de pele clara e o fortalecimento do movimento negro ciberativista na Paraíba - Costa, Mariana Cruz e Silva da (2022)
The research aims to define the concepts of identity, race, miscegenation and cyberactivism, with the objective of studying the strengthening of the cyberactivist Black movement, from the formation of the identity of light-skinned black women. Mixed-raced black women who produce content and cyberactivism in the cities of João Pessoa, Campina Grande and Santa Rita were invited to be interviewed, using the virtual ethnography method on the digital platform Instagram. The research, therefore, intends to present answers to the identity problem of mixed-race women - due to racism and the myth of Brazilian racial democracy - who stick to the Black cyberactivist movement, from the moment they identify as black.